CLINICAL CHARACTERISTICS, MOTOR AND NON-MOTOR COMPLICATIONS, AND QUALITY OF LIFE OF PARKINSON’S DISEASE PATIENTS - Maryanti, Yossi; Sukiandra, Riki; Juananda, Desby; Lestari, Enny; Octaria, Allysa; Andrilla, Faiza; Zahira, Mifta; Putri, Reta Amelia (MNJ (Malang Neurology Journal), 2026)
Background: Parkinson’s disease is a chronic and progressive neurodegenerative disorder characterized by both motor and non-motor symptoms that worsen over time, ultimately reducing patients’ quality of life. Objective: This study aimed to describe the clinical characteristics, motor and non-motor complications, and quality of life of Parkinson’s disease patients treated at Arifin Achmad Regional General Hospital, Riau. Methods: This study was a descriptive cross-sectional study conducted at the Neurology Polyclinic of Arifin Achmad Regional General Hospital, Riau, from January to August 2025. Samples were obtained using a total sampling technique. Results: A total of 31 Parkinson’s patients were included. More than half (54.8%) were aged ≥ 60 years, and 51.6% were males. Most had a high school education (32.3%), were unemployed (90.3%), and were not engaged in social activities (61.3%). The majority had no family history of Parkinson’s disease (83.9%) but presented with comorbidities (54.8%). Tremor was the predominant symptom (96.8%), while 67.7% had no motor complications. Cognitive impairment was found in 45.2%, mainly affecting the memory domain (96.8%). Poor sleep quality was common (61.3%), with nocturia as the most frequent disturbance (90.3%). Regarding quality of life, 32.3% of patients were within the acceptable range, with the mobility domain being the most affected (48.4%). Conclusion: Most Parkinson’s patients were elderly males with moderate disease progression. Comprehensive management addressing both motor and non-motor symptoms is essential to improve patients’ overall quality of life.